2007
DOI: 10.1002/ird.323
|View full text |Cite
|
Sign up to set email alerts
|

Efficient irrigation; inefficient communication; flawed recommendations

Abstract: Concerns about scarcity of water have focused attention on irrigation, the largest water-using sector worldwide, which is widely seen as a low-value, wasteful and ''inefficient'' use for water. The terminology for this debate is, however, poorly defined -often failing even to distinguish between consumptive and non-consumptive uses. In consequence, technical interventions have not always led to the expected, desirable outcomes, and the recommendations in many reports and papers are at best dubious, at worst si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(122 citation statements)
references
References 10 publications
0
121
0
1
Order By: Relevance
“…However, Irrigation performance indices that take into account the productive or economic results of the water devoted to irrigation are increasingly gaining interest. This is the case of the water productivity lindex proposed by Perry (2007) The irrigation water productivity can be expressed either in terms of yield (kg/m 3 ) or in terms of economic returns (€/m 3 ) (Malano et al 2004;Pande et al 2012;Yihun et al 2013;Martínez and Reca 2014).…”
mentioning
confidence: 99%
“…However, Irrigation performance indices that take into account the productive or economic results of the water devoted to irrigation are increasingly gaining interest. This is the case of the water productivity lindex proposed by Perry (2007) The irrigation water productivity can be expressed either in terms of yield (kg/m 3 ) or in terms of economic returns (€/m 3 ) (Malano et al 2004;Pande et al 2012;Yihun et al 2013;Martínez and Reca 2014).…”
mentioning
confidence: 99%
“…Considering these differences, the water and salt management practices at the two case studies were discussed. According to the mean water use efficiency (ET/R+I) (Perry, 2007;Heydari, 2014), less water was applied than used by the crop with objective scheduling during the winter (1.17) and summer (1.19) seasons compared to subjective scheduling (0.88 during winter and 0.99 during summer). This was possible because rainfall and the groundwater table were utilized better as sources of water for crop water requirements.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ostrom report [7], there is an almost threefold increase in the total area of irrigated agriculture during the past century. Perry's study [8] also indicated that 20 % of total cropland (irrigated agriculture) produces more than 40 % of the world's total agricultural output. Therefore, expansion of irrigated agricultural areas is essential in nation-building processes [9].…”
Section: Introductionmentioning
confidence: 99%